One year of interdisciplinary therapy decreases predictors and prevalence of sleep-breathing disorder in obese adolescents. - Corgosinho, Flávia Campos; Dâmaso, Ana Raimunda; Tufik, Sergio; de Piano, Aline; Sanches, Priscila de Lima; Campos, Raquel Munhoz da Silveira; Silva, Patrícia Leão; Carnier, June; Tock, Lian; Andersen, Monica Levy; et al. (Journal of Health & Biological Sciences, 2015)
Obesity is considered a chronic sub-inflammatory disease, being a risk factor for many diseases such as Sleep-Breathing Disorder (SBD). Although, the interaction between obesity and sleep has been explored lately, not much is known in the adolescent population. Thus the aims of this study were threefold: first, to determine the prevalence of SBD in a sample of Brazilians’ obese adolescents; second, to assess the effect of weight loss therapy on sleep, metabolic and inflammatory parameters; third, to compare sex-differences between the adolescents. A total of 55 obese adolescents were submitted to one year of interdisciplinary weight loss therapy. Sleep, anthropometric, metabolic and inflammatory profiles were evaluated at baseline and after one year of therapy. At the beginning of the treatment, 21.9% of the obese adolescents presented SBD, whereas only 8.9% did so after intervention. The weight loss therapy was able to improve significantly the metabolic, inflammatory markers, and sleep pattern in both genders. Negative correlation was found between leptin and REM sleep, but only in boys. Positive correlations were found between body fat (kg) with respiratory events (r=0.48) and the respiratory disturbance index (r=0.49). Boys presented significant higher prevalence of sleep-breathing disorders. Our results support the importance of an early intervention as a strategy to prevent and control obesity and its comorbities, showing a decrease in SBD, visceral adiposity and other parameters.